2016
DOI: 10.1016/j.bpj.2016.03.029
|View full text |Cite
|
Sign up to set email alerts
|

The In Situ Tryptophan Analogue Probes the Conformational Dynamics in Asparaginase Isozymes

Abstract: Dynamic water solvation is crucial to protein conformational reorganization and hence to protein structure and functionality. We report here the characterization of water dynamics on the L-asparaginase structural homology isozymes L-asparaginases I (AnsA) and II (AnsB), which are shown via fluorescence spectroscopy and dynamics in combination with molecular dynamics simulation to have distinct catalytic activity. By use of the tryptophan (Trp) analog probe 2,7-diaza-tryptophan ((2,7-aza)Trp), which exhibits un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Notably, recent work demonstrated that an energy restraint ensemble on the coarse-graining (CG) models is necessary to avoid overinterpretation of experimental SAXS data by spurious conformational representations. Naturally, the protein structure dictates the features of internal loop motions collectively on the nanosecond time scale. ,, In MD simulations, periodic boundary conditions and long-range hydrodynamic interactions can introduce an effective coupling between the protein and explicit water solvent, and their diffusive coordinate motions. In the present study, the explicit water-coupled protein dynamics with the ∼1 μs trajectory demonstrates a rich conformational landscape of adequate sampling for the validation of MD conformations of solution X-ray scattering.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, recent work demonstrated that an energy restraint ensemble on the coarse-graining (CG) models is necessary to avoid overinterpretation of experimental SAXS data by spurious conformational representations. Naturally, the protein structure dictates the features of internal loop motions collectively on the nanosecond time scale. ,, In MD simulations, periodic boundary conditions and long-range hydrodynamic interactions can introduce an effective coupling between the protein and explicit water solvent, and their diffusive coordinate motions. In the present study, the explicit water-coupled protein dynamics with the ∼1 μs trajectory demonstrates a rich conformational landscape of adequate sampling for the validation of MD conformations of solution X-ray scattering.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, mainly due to the lack of an X-ray crystallographic structure, information relevant to the structure–functionality relationship of TXAS is still rather limited. Alternatively, molecular modeling and spectral binding assays have been implemented in predicting the active site and its mechanism of metabolism. When implemented in combination with other data, such as intermolecular ligand binding, optical probes are also extremely useful in the determination of molecular complexes and protein microenvironments. ,,, Evidently, these models require the construction of a three-dimensional representation of TXAS in order to probe the nature and the structural properties responsible for its specific functionality. , The protein interaction sites/heme active site, which can be determined from the protein model, have been further scrutinized by optical probes in a bid to enhance their predictive probability. , Nevertheless, these models have to be verified by either crystallization or site-directed mutagenesis experiments, in which the increasing number of P450 crystal structures would facilitate the homology modeling efforts. Therefore, assessment of the quality of data and structures is of utmost importance, particularly when automation protocols are employed to assess the consistency of the data directly by information theoretical methods. …”
Section: Introductionmentioning
confidence: 99%
“…It appears that one can acquire a more fundamental understanding of the very complicated respiration processes by applying the super-Arrhenius kinetic and reaction modeling on a molecular level. An important remark regarding the MD simulations is that these dynamics of structural modulation involve a locally-constrained environment of protein and the trapped-water motion within the channel 54 . The trapped-water motion takes place in different ways, and our interest lies in how such water molecules in the active or effector site could be regulated in different channels with different structural states in terms of water diffusion in the channels.…”
Section: Discussionmentioning
confidence: 99%
“…They found that this compound provided dual emission peaks at 335 and 495 nm in neutral water, indicating the occurrence of an ESInterPT process through an intermolecular H-bond wire of water. Thus, 2,7-DAI could be potentially used as an optical probe for the surrounding water environment of proteins. , Its photophysical properties in aqueous environment from experiment were confirmed by theoretical calculations using microsolvation on top with an implicit solvent model. , The dual emission peaks were suggested from N* around 305–338 nm and T* around 419–469 nm. , For ESInterPT, the multiple PT processes of 2,7-DAI­(H 2 O) n (where n = 1–2) using microsolvation on top with an implicit solvent model considering only the one hydration shell have been theoretically reported. , The multiple PT reactions of 2,7-DAI­(H 2 O) 1 and 2,7-DAI­(H 2 O) 2 occurred with rather high PT barriers (>6 kcal/mol) in the S 1 state through intermolecular H-bonds of water wire. However, the experiment confirmed the occurrence of ESInterPT in 2,7-DAI in a water environment; hence, using only one hydration shell to describe the PT behavior might not be enough for description of the ESInterPT process in bulk water.…”
Section: Introductionmentioning
confidence: 89%